Manga arrive! (Journal of Parents and Teachers, 2014)
In order for children to read, we allow them to pick up any story that falls into their hands. Currently, the Manga invade kiosks, and not all are recommended or suitable for children. This article offers a list of Mangos appropriate for them.
Keywords: Manga; reading; appropriate.